CREATION OF UNIVERSITY BIOINDUSTRIES FOR COOPERATIVE COMPETITION: SOCIAL DEVELOPMENT MODEL - Argota-Pérez, George (2021)
The aim of the study was to evaluate the creation of university bioindustries for cooperative competition from a social development model. Th e study was carried out in October 2021 where it was selected, the Faculty of Pharmacy and Biochemistry of the National University ¨San Luis Gonzaga, Ica-Peru. Based on a pilot population study carried out in the "Arenales" Wholesale Market (14°04’04.0”S 75°43’43.0”W) on the nutritional consumption of fruits and vegetables in the city of Ica, Peru, the determination of polyphenols was considered from a teaching laboratory practice and then, that is valued towards a development model and that begins with the selection of accessions, physical and chemical treatments until the bioactive is obtained for its commercialization. Together with the determination in fruits and vegetables of primary metabolites such as lipids, carbohydrates, proteins and vitamins, there is also the determination of secondary metabolites such as polyphenols that can be encapsulated which allows a closed cycle of the product for the creation of bioindustries in the university.